2012
DOI: 10.3382/ps.2011-02131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic, Clostridium butyricum, on growth performance, immune function, and cecal microflora in broiler chickens

Abstract: Four hundred and fifty 1-d-old male Lingnan Yellow broiler chickens were used to investigate the effects of Clostridium butyricum on growth performance, immune function, and cecal microflora. The birds were randomly assigned to 5 treatments and offered the same antibiotic-free basal diets for 42 d. The treatments were as follows: no addition (control), 1 × 10(7) cfu C. butyricum/kg of diet (CB1), 2 × 10(7) cfu C. butyricum/kg of diet (CB2), 3 × 10(7) cfu C. butyricum/kg of diet (CB3), and 10 mg of colistine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(182 citation statements)
references
References 45 publications
12
168
1
1
Order By: Relevance
“…found that BWG was increased by the administration of 10 5 and 10 8 CFU/kg of Bacillus-based probiotic. Yang et al (2012) found that adding 2 × 10 7 CFU or 3 × 10 7 CFU/kg of Clostridium butyricum to the diet improved the ADG in broiler chickens. Similar positive effects were also reported by other researchers (Talebi et al 2008;Zhou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…found that BWG was increased by the administration of 10 5 and 10 8 CFU/kg of Bacillus-based probiotic. Yang et al (2012) found that adding 2 × 10 7 CFU or 3 × 10 7 CFU/kg of Clostridium butyricum to the diet improved the ADG in broiler chickens. Similar positive effects were also reported by other researchers (Talebi et al 2008;Zhou et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rearing condition, probiotic dosage, bird's age as well as the delivery method (water or feed) can also affect broilers performance and gut bacterial responses to this feed additive (Yang et al, 2009). Hence, it is difficult to compare the results of different studies (Yang et al, 2012). All above-mentioned factors probably can explain the contrasting results in the performance of broilers fed with probiotic and prebiotic.…”
Section: Performance and Cecal Bacteria Counts Of Broilers Fed Low Prmentioning
confidence: 68%
“…Supplementation with probiotics and prebiotics can improve the performance of broiler chickens (Kim et al, 2011;Yang et al, 2012;Houshmand et al, 2012b;Salim et al, 2013;Bozkurt et al, 2014). Also, their positive effects on protein utilization have been indicated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Clostridium butyricum has been shown effective as a poultry probiotic [48]. In addition, other butyrate producing bacteria such as Faecalibacterium prausnitzi, Roseburia faecis, and others may be associated with an healthy intestinal tract due the beneficial properties of this short chain fatty acid [49,50].…”
Section: Effect Of Time and Treatments On Abundance Of Pioneer Colonimentioning
confidence: 99%